EVALUATION OF BIOMECHANICAL EFFECTS OF PROSTHETIC COMPONENTS WITH DIFFERENT MATERIALS ON THE ABUTMENT SCREW - Gonca Deste Gökay; Gülsüm Gökçimen; Rukiye Durkan (Cumhuriyet University, 2022)
Objectives: The purpose of this study was to evaluate the effects of different resin-based and ceramic superstructure materials and two different abutment types on the stress distribution of the abutment screw using the three-dimensional finite element stress analysis method. Materials and Methods: A three dimensional implant, abutment (zirconia and titanium), abutment screw, crown (zirconia reinforced lithium silicate, lithium disilicate, polymer-infiltrated resin ceramic, and PEEK), and alveolar bone were designed using Rhinoceros 3D modeling software and VRMesh Studio software and combined to form 8 simulations. On the models prepared, loading was made on the lingual tubercule of the maxillary right first premolar crown at an angle of 30° with 150 N force obliquely in the buccolingual direction. The von Mises values obtained from the abutment screw were compared according to the types of abutment and crown materials. Results: The von Mises stress values in the abutment screw were higher in the models using a titanium abutment abutment (on average 1336.24 MPa), and the lower stress values were obtained in the models using a zirconia abutment (on average 964.26 MPa). When the prosthetic material used was changed, no apparent difference was observed in the stress values on the abutment screw. Conclusions: Considering that the abutment screw is the weakest link of the implant system, zirconia abutments can be used reliably in the maxillary first premolar region where aesthetic expectations are high.